Coding of social novelty in the hippocampal CA2 region and its disruption and rescue in a 22q11.2 microdeletion mouse model - Donegan, Macayla L; Stefanini, Fabio; Meira, Torcato; Gordon, Joshua A; Fusi, Stefano; Siegelbaum, Steven A (Nature neuroscience, 2020)
The hippocampal CA2 region is essential for social memory. To determine whether CA2 activity encodes social interactions, we recorded extracellularly from CA2 pyramidal neurons (PNs) in male mice during social behavior. Although CA2 neuronal firing showed only weak spatial selectivity, it accurately encoded contextual changes and distinguished between a novel and a familiar mouse. In the Df(16)A mouse model of the human 22q11.2 microdeletion, which confers a 30-fold increased risk of schizophrenia, CA2 social coding was impaired, consistent with the social memory deficit observed in these mice; in contrast, spatial coding accuracy was greatly enhanced. CA2 PNs were previously found to be hyperpolarized in Df(16)A mice, likely due to upregulation of TREK-1 K current. We found that TREK-1 blockade rescued social memory and CA2 social coding in Df(16)A mice, supporting a crucial role for CA2 in the normal encoding of social stimuli and in social behavioral dysfunction in disease.